Effects of Sintering Behavior on Structure and Properties of B2O3 doped (Bi0.5Na0.5)0.94Ba0.06TiO3 Lead-Free Ceramics - Manotham, Supalak; Jaita, Pharatree; Tunkasiri, Tawee; Rujijanajul, Gobwute (Asian Health, Science and Technology Reports, 2016)
The effect of sintering temperature on phase structure, densification and room temperature dielectric properties of B2O3 doped (Bi0.5Na0.5)0.94Ba0.06TiO3(BNBT) lead-free ceramics prepared by a solid-state mixed oxide method was investigated and presented in this work. The X-ray diffraction analysis of the ceramics suggests that all samples exhibited a single perovskite structure without any secondary phase. The coexisting of both rhombohedral and tetragonal phases was identified over the entire sintering temperature range. The optimum sintering temperature for preparation of high-density BNBT + 2 wt% B2O3 ceramic was found to be 1050°C. Room temperature dielectric measurement data showed that the dielectric constant and dielectric loss values were increased with increasing the sintering temperature.